Pengaruh Motivasi dan Beban Kerja Terhadap Kepuasan Kerja Pegawai pada Dinas Pekerja Umum (PU) Kota Bima - Rajulio Lopes; Muhammad Yusuf; Amirulmukminin Amirulmukminin (Indo Publishing, 2026)
This study aims to examine and analyze the effect of motivation and workload on employee job satisfaction at the Public Works Office (Dinas Pekerjaan Umum) of Bima City, both partially and simultaneously. This research employed an associative research design with a quantitative approach. The population consisted of 126 employees, while the sample comprised 60 civil servants selected using a purposive sampling technique. Data were collected through observation, questionnaires, and literature review. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, t-test, and F-test with the assistance of SPSS software. The results of the study indicate that motivation has a positive and significant effect on employee job satisfaction, with a t-value of 3.306 and a significance value of 0.002 (<0.05). Workload has a negative and significant effect on job satisfaction, with a t-value of -2.213 and a significance value of 0.031 (<0.05). Simultaneously, motivation and workload have a significant effect on employee job satisfaction, as indicated by an F-value of 18.181 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) is 0.589, indicating that 58.9% of the variation in employee job satisfaction is explained by motivation and workload, while the remaining 41.1% is influenced by other factors not examined in this study. Based on the findings, it can be concluded that higher motivation contributes to increased employee job satisfaction, whereas excessive or inappropriate workload tends to reduce job satisfaction. Therefore, the Public Works Office of Bima City is expected to enhance employee motivation and manage workload proportionally to improve employee job satisfaction.